PENGARUH KEPEMIMPINAN, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PRODUKSI PT. KARTIKA POLASWASTI MAHARDHIKA - Asah Wiari Sidiq; Asih Niati; Cholid Muzakki (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2021)
The problem that forms the basis of this research is where the production employees of PT.Kartika Polaswasti Mahardhika is not able to reach the target that has been charged so that theperformance of the employees experienced a decline in employee performance and this studyaimed to analyze leadership factors, compensation and work environment on the performance ofemployees. The population in this study were all employees of PT. Kartika Polaswasti Mahardhikawhich amounted to 437 employees while the sampling technique used was a non probabilitysampling technique with the type of accidental sampling and the analysis tool used in this studymultiple linear regression. The results showed that leadership variables, compensation and workenvironment had a positive and significant effect on the performance of employees of PT.Polaswasti Mahardhika Kartika and the results of the adjusted R square value in the regressionmodel were obtained at 0.571 which means that 57.1 percent of employee performance variablescan be explained by leadership variables, compensation and work environment while theremaining 42.9 percent is explained by other variables outside of this study.